A taxonomic revision of Centaurea sect. Microlophus (Asteraceae, Cardueae–Centaureinae) and three new records for the flora of Iran. (9th February 2015) - Negaresh, Kazem; Rahiminejad, Mohammad Reza
<x xml:space="preserve">Abstract</x> A global taxonomic revision, lectotypifications and neotypifications of Centaurea L. sect. Microlophus (Cass.) DC. (Asteraceae) are presented. The recognized species, the relevant synonyms, type details, examined specimen lists, full descriptions and a taxonomic key are provided for this section. The geographic distribution of all the 9 species recognized is mapped. Centaurea alveicola Rech. f., C. rigida Banks & Sol. and C. polypodiifolia Boiss. var. szovitsiana (Boiss.) Wagenitz are reported as new to the flora of Iran.